Intermetallic compound layer and fatigue crack evolution of Bi-contained Sn-1.0Ag-0.5Cu solder under thermal aging and thermal fatigue - Junjie Zhao; Jun Wu; Jiayu Zhang; Mingqin Liao; Fengjiang Wang (Journal of Materials Research and Technology)
The Sn-1.0Ag-0.5Cu-xBi solder joints with different Bi content were prepared by reflow soldering. The shear strength, intermetallic compound layer, and fatigue evolution in solder joints were then investigated under thermal aging and thermal fatigue. During isothermal aging, the size of Sn grain and intermetallic compound (IMC) thickness in solder joints were greatly decreased due to the addition of Bi, especially with 5 wt% addition because the atomic migration to produce IMC layer was hindered by the Bi diffusion layer formed at the IMC interface, which means that Bi can play a role in refining the grains. Meanwhile, the shear strength of Sn-1.0Ag-0.5Cu-xBi solder joints was greatly improved through solid solution strengthening. During thermal cycling, electron backscatter diffraction analysis showed that Bi addition increased the tendency of grains to slip, as indicated by a higher Schmid factor. The thermal fatigue failure modes of micro solder joints with various Bi contents were different. In the absence of Bi addition, the fracture mode of the solder joint was typical transgranular fracture mode. With the addition ofBi element, the solder joints showed an intergranular fracture mode. The addition of Bi provides more heterogeneous nucleation sites for fine recrystallized grains, and the fracture mode was changed due to the formation of a high number of recrystallized grains. The recrystallized grains evolved from the continuous recrystallization process of sub-grain rotation under the influence of thermal-mechanical stress and the discontinuous recrystallization process of deformation storage.